"Let me be dust": Memory beyond testimony in Gwangju, South Korea. (June 2023) - Karp, Melissa
Archives of the 5·18 Gwangju People's Uprising—a 1980 pro-democracy protest in South Korea—entered UNESCO's Memory of the World Register in 2011. UNESCO's inclusion provided international recognition for the Uprising after censorship under the Chun Doo-hwan regime; however, the narrative clarity presented through photographs, documents, and testimony in the museum now defines and limits memorialization. By contrast, Ch'oe Yun's 1988 novella There a Petal Silently Falls imagines what lies beyond archives. With its silent protagonist and fragmented, sometimes illegible prose, Petal interrogates the coherence of memory when stripped of testimony. Reading Petal and the Archives as distinct memory sites, this article questions how memory projects privilege evidentiary archives, which might perpetuate the very patterns of violence such projects seek to uncover. As human rights ideologies become increasingly predominant, Ch'oe's novella reasserts not only that the agony of memory can exceed the intelligibility of the archive, but that it must .